PERAN PENYULUH PERTANIAN TERHADAP KINERJA USAHATANI PADI SAWAH DI DESA TEPPOE KECAMATAN POLEANG TIMUR KABUPATEN BOMBANA - Bahtiar, Bahtiar; Salahuddin, Salahuddin; Jayadisastra, Yoenita (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
This study aims to examine the role of agricultural extension workers in the context of wet-rice farming in Teppoe Village, East Poleang Subdistrict, and to elucidate the relationship between the two. The research population consisted of all wet-rice farmers in Teppoe Village, amounting to a total of 250 individuals. A sample of 25 individuals was selected from the total research population, representing 10% of the total number of respondents. The data were collected via survey, interview, and documentation methods with the assistance of research instruments in the form of questionnaires. This study employs a quantitative approach. The research data were analyzed using quantitative descriptive methods, specifically the class interval formula and Spearman's rank correlation. The findings indicated that the role of agricultural extension workers in Teppoe Village, East Poleang Subdistrict, as facilitators was deemed to be satisfactory. However, their roles as motivators and educators were perceived to be inadequate, while their role as innovators was considered to be satisfactory. The performance of paddy rice farming in terms of productivity is in the satisfied category, while the sales price of paddy rice and farmers' income are in the moderately satisfied category. The relationship between the role of agricultural extension officers and farm performance was found to be statistically significant (value 0.031), though the strength of the relationship was relatively weak (value 0.363).